(untitled) (Revista Brasileira Multidisciplinar, 2026)
Hemotherapy is a treatment carried out through transfusion, with extensive action by the nursing team throughout the procedure. The objective of this study was to search in the literature for the main nursing care measures present in transfusion reactions. This is an integrative review of the literature, in the databases, Web of Science; National Library of Medicine, Scopus and Cumulative Index to Nursing and Allied Health Literature and via the Virtual Health Library portal. Eight studies were selected, predominantly: Knowledge and construction of the nursing team regarding transfusion reactions; Identification of nursing knowledge through continuing education; Transfusion-associated circulatory overload and transfusion-related acute lung injury. It was concluded that the nursing team needs training on the transfusion process for quality nursing care during the transfusion reaction, with the construction of safe practices in the administration of blood components.